2012
DOI: 10.4103/2231-0762.109367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating dental awareness and periodontal health status in different socioeconomic groups in the population of Sundernagar, Himachal Pradesh, India

Abstract: Context:Survey.Aims:To evaluate dental awareness and periodontal health status in different socioeconomic groups in the population of Sundernagar, Himachal Pradesh, India.Settings and Design:Cross-sectional study.Malerials and Methods:This cross-sectional study was conducted in 300 patients with different socioeconomic status who visited Himachal Dental College, Sundernagar, and Dental OPD of the Civil Hospital, Sundernagar. Mouth mirror, CPI probe, and illuminated light source were used for examination. Perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Besides these fi ndings observed in adults, a review also highlights that maintaining good oral hygiene in children with autism is a diffi cult task both for the parents of the child, and the dental staff because of the lack of interest by these children, hypersensitivity to various stimulus and lack of necessary manual dexterity. [9] Furthermore, our study showed that 58.36% of the subjects visited a dentist only when they felt pain [ Table 9 and Chart 9] and this was found to be statistically signifi cant, which is similar to the study done by Gautam et al [10] in Himachal Pradesh where majority of the participants did not visit a dentist especially people belonging to lower socio-economic status. This clearly shows that standards of oral health care are very poor not only in Jaipur, but also in our whole country where majority of the population is aff ected due to poor socio-economic status.…”
Section: Discussionsupporting
confidence: 84%
“…Besides these fi ndings observed in adults, a review also highlights that maintaining good oral hygiene in children with autism is a diffi cult task both for the parents of the child, and the dental staff because of the lack of interest by these children, hypersensitivity to various stimulus and lack of necessary manual dexterity. [9] Furthermore, our study showed that 58.36% of the subjects visited a dentist only when they felt pain [ Table 9 and Chart 9] and this was found to be statistically signifi cant, which is similar to the study done by Gautam et al [10] in Himachal Pradesh where majority of the participants did not visit a dentist especially people belonging to lower socio-economic status. This clearly shows that standards of oral health care are very poor not only in Jaipur, but also in our whole country where majority of the population is aff ected due to poor socio-economic status.…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that the socioeconomic status of individuals has an impact on their periodontal treatment needs and knowledge of oral health (23). There is a negative correlation between the financial income and education level of our participants with CPI values.…”
Section: Discussionmentioning
confidence: 56%
“…It comprises of change in attitude of people toward oral health, prevention, timely and appropriate diagnosis, and professional care seeking as and when required. 7 There is scarcity of epidemiological data on representative urban population. Thus, the present study was undertaken on schoolchildren of low socioeconomic area of Mumbai city to find the prevalence of oral morbidities and the unmet need for oral health services by assessing the existing health-seeking behavior for these morbidities.…”
Section: Introductionmentioning
confidence: 99%